How can applied theatre be implemented to address male adolescents' perceptions of their female counterparts? A case study of adolescent boys at Izenzo Kungemazwi Community College - Molefe, Butana P. (My University, 2014)
Gender based sexual violence against women has become epidemic in South Africa. This study attempts to explore the pedagogical approach of Applied Drama as a qualitative behavioural change programme for adolescent black males. This Practice-based Research Report investigates the efficacy of Applied Drama as a tool to address male adolescent perceptions toward their female counterparts, with particular reference to the case study of Izenzo Community College, Hillbrow, South Africa. The research consisted of a Participation Action Research exploration in three phases over a year, culminating in a Practice-based examination and followed by this written research report. The study argues that Applied Drama is a powerful tool to encourage dialogue amongst adolescent males about complex subject-matter. Chapter One introduces the reader to Izenzo, the framework of the study, and the narrative of the researcher/facilitator. Chapter Two interrogates masculinities in contemporary South Africa. Chapter Three introduces the research problem and methodology, and Chapter Four discusses the two initial phases of research. This highlights the trajectory of research that resulted in the final phase of research that is explored in detail in Chapter Five. Chapter Six analyses the nature of Applied Drama in relation to masculinities. This study affirms the role of Applied Drama as a meaningful approach to tackling the rising crisis of gender based sexual violence in South Africa. It emphasises the central role of the facilitator as the implementer of Applied Drama as a facilitation process that enhances dialogue for change.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, Dramatic Arts, 2013
Keywords: adolescents; masculinity; gender based violence; sessions